2022
DOI: 10.1080/02670844.2022.2148452
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification in the shape of a pattern using crepe paper maskant in EDM

Abstract: This article describes a new approach of surface modification in the shape of a pattern employing powder metallurgical (PM) green compact tool and electrical discharge machining (EDM). Patterns on the workpieces of aluminium (Al) 6061 are generated using PM green tools and crepe paper masking technique in EDM. The tool material is made of copper and tungsten powders. The pattern surface is analyzed by evaluating the output performance. The presence of electrode material in the pattern surface is identified, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The algorithm can be classified into two distinct phases: The 'Teachers phase' and the 'Learner Phase'. 12 In a typical scenario, the teacher is often considered highly competent within the group and shares their knowledge with the students during this phase. The teacher imparts knowledge to the students while striving to enhance the collective performance average of the students.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The algorithm can be classified into two distinct phases: The 'Teachers phase' and the 'Learner Phase'. 12 In a typical scenario, the teacher is often considered highly competent within the group and shares their knowledge with the students during this phase. The teacher imparts knowledge to the students while striving to enhance the collective performance average of the students.…”
Section: Methodsmentioning
confidence: 99%
“…6 Though both processes have an impact in the field of EDM deposition but studies have shown that the PM tool offers precise control over the distribution of particles, ensuring uniformity in deposition. 7 Previous research has reported the effective deposition of materials such as silicon carbide, 8 titanium di-boride, 9 tungsten carbide, 10 MWCNT, 6 copper-nickel, 11 tungsten, 12 tungsten disulphide, 13,14 hexagonal boron nitride, 4 molybdenum disulphide, 15 etc. Therefore, it indicates that EDM is a suitable tool for material deposition operation.…”
Section: Introductionmentioning
confidence: 99%